Integrating Communication and Stakeholder Engagement for Strengthening Public Islamic Education Services - Saifullah; Siti Nur Janah; Nelma Elpayuni; Romlah; Ali Abdul Wakhid (Journal of Educational Management Research, 2025)
This study examines the role of communication and stakeholder engagement in enhancing public services in Islamic education institutions. The purpose of this research is to analyze how integrating communication strategies and stakeholder participation can strengthen the management and effectiveness of public Islamic education services. A qualitative, descriptive-analytical approach was employed, drawing on secondary sources and conceptual studies of organizational communication, stakeholder management, and Islamic education governance principles. The analysis involved inductively interpreting data to identify patterns of interaction between communication, stakeholder involvement, and service quality improvement. The results indicate that effective communication and active stakeholder involvement are crucial for enhancing public services in Islamic education. Open, honest, and two-way communication fosters a harmonious work environment, builds trust among institutional members, and accelerates problem-solving. Stakeholder participation, both internal and external, provides moral, social, and oversight support, increasing accountability and legitimacy in the eyes of the community. The integration of communication and stakeholder engagement creates a transparent, adaptive, and sustainable governance system that embodies Islamic values such as shura, amanah, tabligh, and ta'awun in educational management practice.